Learning to Teach with Mathematics Textbooks: How Preservice Teachers Interpret and Use Curriculum Materials - Nicol, C.; Crespo, S. (Educational Studies in Mathematics, 2006)
This study investigates how four prospective teachers interpret and use textbooks while learning to teach mathematics during university coursework and practicum teaching. Results indicate that prospective teachers had varied approaches to using textbooks ranging from adherence, elaboration, and creation. Factors influencing how they engaged with texts include their practicum classroom setting, access to resources, and their understanding of mathematics. Preservice teachers' attempts to modify textbook lessons raised pedagogical, curricular, and mathematical questions for them that were not easily answered by reference to the textbooks or teacher's guides. Findings indicate that the practicum can, however, challenge preservice teachers to be creative and flexible users of curriculum materials.
Keywords: INSTRUCTIONAL systems; INTERNS (Education); MATHEMATICS -- Equipment & supplies; MATHEMATICS -- Study & teaching (Elementary); Mathematics Education; OCCUPATIONAL training; PRACTICUMS; STUDENT teachers; TEACHING aids & devices; curriculum materials; elementary teacher education; preservice elementary teachers; textbooks